2019
DOI: 10.1063/1.5123188
|View full text |Cite
|
Sign up to set email alerts
|

Inclined hydromagnetic impact on tangent hyperbolic fluid flow over a vertical stretched sheet

Abstract: The current research aims to examine the impact of a tangent hyperbolic fluid flow confined by a stretching sheet with the existence of variable thermal conductivity, mixed convection, and magneto hydrodynamics. A mathematical model is developed in the form of partial differential equations (PDEs) and then converted into ordinary differential equations by using self-felicitous transformations. The technique of BVP4C (MATLAB package) has been used to simplify these ordinary differential equations. The numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The impact of MHD tangent hyperbolic fluid past a stretching sheet in the presence of a convective boundary is studied by Hussain et al, [18]. Ali et al, [19] have examined the effect of MHD on tangent hyperbolic fluid flow past a stretched sheet. Ibrahim [20] has discussed the MHD and radiation effects on tangent hyperbolic nanofluid past a stretching sheet and showed that radiation upturns the thickness of the thermal boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of MHD tangent hyperbolic fluid past a stretching sheet in the presence of a convective boundary is studied by Hussain et al, [18]. Ali et al, [19] have examined the effect of MHD on tangent hyperbolic fluid flow past a stretched sheet. Ibrahim [20] has discussed the MHD and radiation effects on tangent hyperbolic nanofluid past a stretching sheet and showed that radiation upturns the thickness of the thermal boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…The implications of radiation on a tangent hyperbolic MHD nanofluid flow across an angled sheet were investigated by Saidulu et al [28] and the sheet contained an exponentially stretching property. Ali et al [29] established some graphical results for tangent hyperbolic fluid over a vertically stretched sheet and the consequence of an angled hydromagnetic field was also discussed. The mathematical model and technical flow characteristics of hyperbolic tangent nanofluid across a cone-shaped surface and a plate were investigated by Bilal et al [30] under mixed convection and the implications of a chemical reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Also, due to recent interest in the behaviour of a non-Newtonian type of fluid, many researchers have investigated the behaviour of this type of fluid by examing the characteristics features of different physical properties. More so, the hydrodynamic impact of inclination on tangent hyperbolic flow was considered by Ali et al [1]. Bilal et al [2] examined Williamson fluid with nanofluid pasted on a stretch sheet.…”
Section: Introductionmentioning
confidence: 99%